Peptidyl‐Prolyl Isomerase 1 Regulates Ca2+ Handling by Modulating Sarco(Endo)Plasmic Reticulum Calcium ATPase and Na2+/Ca2+ Exchanger 1 Protein Levels and Function - Veronica Sacchi; Bingyan J. Wang; Dieter Kubli; Alexander S. Martinez; Jung‐Kang Jin; Roberto Alvarez; Nirmala Hariharan; Christopher Glembotski; Takafumi Uchida; James S. Malter; Yijun Yang; Polina Gross; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundAberrant Ca2+ handling is a prominent feature of heart failure. Elucidation of the molecular mechanisms responsible for aberrant Ca2+ handling is essential for the development of strategies to blunt pathological changes in calcium dynamics. The peptidyl‐prolyl cis‐trans isomerase peptidyl‐prolyl isomerase 1 (Pin1) is a critical mediator of myocardial hypertrophy development and cardiac progenitor cell cycle. However, the influence of Pin1 on calcium cycling regulation has not been explored. On the basis of these findings, the aim of this study is to define Pin1 as a novel modulator of Ca2+ handling, with implications for improving myocardial contractility and potential for ameliorating development of heart failure. Methods and ResultsPin1 gene deletion or pharmacological inhibition delays cytosolic Ca2+ decay in isolated cardiomyocytes. Paradoxically, reduced Pin1 activity correlates with increased sarco(endo)plasmic reticulum calcium ATPase (SERCA2a) and Na2+/Ca2+ exchanger 1 protein levels. However, SERCA2a ATPase activity and calcium reuptake were reduced in sarcoplasmic reticulum membranes isolated from Pin1‐deficient hearts, suggesting that Pin1 influences SERCA2a function. SERCA2a and Na2+/Ca2+ exchanger 1 associated with Pin1, as revealed by proximity ligation assay in myocardial tissue sections, indicating that regulation of Ca2+ handling within cardiomyocytes is likely influenced through Pin1 interaction with SERCA2a and Na2+/Ca2+ exchanger 1 proteins. ConclusionsPin1 serves as a modulator of SERCA2a and Na2+/Ca2+ exchanger 1 Ca2+ handling proteins, with loss of function resulting in impaired cardiomyocyte relaxation, setting the stage for subsequent investigations to assess Pin1 dysregulation and modulation in the progression of heart failure.